Islamic Religious Education Literacy and Numeration In the Perspective of the Al-Quran and Hadith - Ainur Rofiq Sofa; Mukni’ah; Mashudi (Journal of Islamic Education Research, 2022)
The word Iqra 'is usually translated as "read.” This understanding follows the word Qara'a, which first meant "gathering.” The Qur'an o.” en uses the word Qara'a in various verses. When he received this sentence the, Prop,het Muhammad trembled and said he could not read. However, this verse’s revelation shows how the highest glorification and assessment of the ability to read and write various sciences is. These verses show that Allah SWT teaches people diverse knowledge, He opens multiple secrets, and He gives different keys to open the treasury of Allah's command, namely with a qalam or pen. Besides tongue reading, Allah also ordained that knowledge can be recorded. The Prophet Muhammad was a person who was not good at reading and writing, but he understood the importance of literacy. Literacy here is the ability to read and write. Including the ability to speak, calculate and solve problems at hand.